EXPLORING THE PSYCHOLOGICAL IMPACTS OF GOOGLE ASSISTANT UTILIZATION FOR EFL STUDENTS: A CASE STUDY - Sephia Difa Adila; Roslaini Roslaini (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
In digital era, technology has become increasingly integrated into the language learning process offering new approaches to address challenges in learning English among EFL students. A recent technological advancement involves the implementation of virtual assistants, such as Google Assistant, as interactive pronunciation coaches for learning speaking. So, this study tries to investigate the psychological impact of using Google Assistant concerning with student’s autonomy, competence, and relatedness as a learning aid among EFL students within the framework of Self-Determination Theory (SDT). A mixed methods approach was used, involving a quantitative survey and qualitative interviews among Students. The questionnaire was adapted from established model of SDT. The results showed that Google Assistant as a learning aid has significantly influenced students’ autonomy, competence, and relatedness in terms of students’ pronunciation, confidence, motivation, and reducing anxiety. These findings implied that integrating voice-based AI aids can be beneficial for learning speaking such as pronunciation instruction, especially for learners with high anxiety or low confidence. To conclude, Google Assistant can serve as an effective interactive pronunciation coach in learning speaking.